Recipes for Recovery: A Configurational Approach to Developing and Deploying Interorganisational Trust Recovery Solutions Following Service Failure - Franklin, Drew (Auckland University of Technology, 2020)
Trust has been described as “perhaps the single most powerful relationship marketing tool available to a company” (Berry, 1995, p. 242). When one party trusts the other, he or she is willing to risk dependence on the other to obtain a goal. Consequently, trust is a critical influence in the development of business-to-business (B2B) relationships and relationship commitment. Trust is a fundamental construct in relational exchange because relationships characterised by trust are so highly valued that parties will desire to commit themselves to such relationships. Trust is also one of the factors that differentiate relationships from mere transactions (Hess & Story, 2005) and enjoys wide acceptance among scholars as a key facilitator of interorganisational relationship development; however, the construct has not been widely explored within the context of service failure. Undeniably, trust is a central tenet of relationship marketing and a useful construct for measuring the likelihood of customer loyalty as well as for predicting future purchase frequency. Many studies have considered how trust develops, but there is limited research specifically investigating how trust might be recovered after it has been harmed in the context of B2B relationships. Scholars note that previous research on business relationships and trust have been largely static, cross-sectional and variable-focused correlational explanations of trust (Huang & Wilkinson, 2013). This shortcoming of current research is that it does not show how different variables change and develop, interrelatedly, and what types of relations emerge, in terms of different mixes and values of variables, under different conditions (Wong, Wilkinson, & Young, 2010). To address this shortcoming, this research features two studies specifically examining trust recovery in B2B relationships following service failure and a breach of trust from the perspective of the buying organisation. Study One presents an exploration of the determinants of trust recovery following service failure through qualitative enquiry and thematic analysis. This analysis reveals eight factors that contribute to trust recovery following service failure of both a cognitive- and affective-dominant nature. Both cognitive- and affective-dominant perceptions are essential causal conditions when seeking to understand buyers’ estimations of trust in a B2B relationship (Franklin & Marshall, 2019) and may be combined in different configurations in order to achieve trust recovery. However, limited research has incorporated these factors to the configurational analysis of high levels of trust recovery success following service failure in a B2B context. Toward this end, Study Two adopts a configurational approach through qualitative comparative analysis (QCA) to investigate the interrelatedness between both causal and contextual conditions when seeking to recover trust with a buying organisation. This analysis unravels configurations of these causal and contextual conditions, offering theoretical consensus surrounding the role of key constituents of interorganisational trust recovery, and their interrelatedness, in a B2B context. This research offers managers guidance regarding different ways to achieve successful trust recovery with their buying organisations. Presenting managers with a variety of optional choices in the design and deployment of reparative solutions invites an economy, or efficiency, in their efforts by choosing the configuration that best fits with the supplying organisation’s strategy, culture or already existing resource availability.
Keywords: Trust; Trust Recovery; Service Failure; Service Recovery; Business-to-Business Marketing; Buyer-Supplier Relationships; Thematic Analysis; Qualitative Comparative Analysis (QCA)